KEBIJAKAN PENGENDALIAN DAN PENGAWASAN MINUMAN BERALKOHOL DI KABUPATEN MINAHASA UTARA PROVINSI SULAWESI UTARA - Wildan Akbar; Mubasysyir Hasanbasri; Retna Siwi Padmawati (Journal of Health Service Management, 2020)
Background: Globally, alcohol use accounts for approximately 3.3 million deaths per year (5.9% of total deaths) and 5.1% disease burden associated with alcohol consumption. Currently, many alcohol abuse occurs in the community that is often known as alcohol abuse. Efforts to minimize the negative impact of consuming alcoholic beverages need to be controlled, supervised, and handling the distribution of alcoholic beverages. Therefore the Government of North Sulawesi issued Local Regulation No. 4 of 2014 on Control and Supervision of Alcoholic Beverages. Objective: This study aimed to see the provision of information and communication related agencies and attitudes implementing in implementing regional regulations number 4 of 2014 on control and supervision of alcoholic beverages. Methods: This research was conducted qualitatively with case study design by snowball sampling method. The number of samples researched as many as 15 respondents. Results: Lack of supervision from the government or related agencies on the control and supervision of alcoholic beverages becomes one of the things to be considered. The provision of information or socialization is conducted erratically and only implemented when there are reports from the public. Communication between relevant agencies is done when it will go down to the field only. The attitude of the policy implementers does not have a neutral attitude towards the community is known there is cooperation between the community with the elements of the relevant agencies to avoid the alcoholic drinks, this becomes the trigger for the community to no longer heed the rules. Conclusion: Implementation of alcoholic beverage control and supervision policy in North Minahasa Regency has not run well and there are still deficiencies and constraints faced. Subsequently, local governments and related agencies should work with communities to improve supervision of the dangers of the effects of alcoholic beverages.